2018
DOI: 10.1016/j.gene.2018.04.027
|View full text |Cite
|
Sign up to set email alerts
|

A case report and review of the literature indicate that HMGA2 should be added as a disease gene for Silver-Russell syndrome

Abstract: Patients with Silver-Russell syndrome (SRS), a syndromic growth retardation syndrome, usually harbor an epimutation at chromosome 11p15 or a maternal uniparental disomy of chromosome 7. However, to date the genetic cause remains unknown in around 40% of SRS cases, suggesting genetic heterogeneity and involvement of other genes. We present a 4-year-old female patient with the clinical diagnosis of SRS and negative results in common genetic SRS diagnostics. Whole exome sequencing identified a de novo heterozygou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…Several genome-wide association studies (GWAS) have outlined HMGA2 as an important factor in determining dimensions in humans, horses and dogs [90][91][92][93][94][95][96][97][98][99][100][101]. Furthermore, Hmga2 mutations have been involved in Silver-Russell syndrome (SRS), or SRS-like syndromes [102][103][104], or ear dimensions in pigs [105]. A search for candidate genes involved in SRS, a rare form of fetal growth retardation usually due to downregulation or malfunctioning of IGF2, has pointed to HMGA2, PLAG1, and IGF2 as genes causally involved, and functional experiments show that HMGA2 promotes IGF2 expression in PLAG1-dependent as well as PLAG1-independent ways; this underlies the significance of this pathway (see also Section 3.2) in the regulation of growth during the fetal and postnatal periods [102] ( Figure 3A).…”
Section: Hmga Dysregulation and Its Impact On Body Sizementioning
confidence: 99%
“…Several genome-wide association studies (GWAS) have outlined HMGA2 as an important factor in determining dimensions in humans, horses and dogs [90][91][92][93][94][95][96][97][98][99][100][101]. Furthermore, Hmga2 mutations have been involved in Silver-Russell syndrome (SRS), or SRS-like syndromes [102][103][104], or ear dimensions in pigs [105]. A search for candidate genes involved in SRS, a rare form of fetal growth retardation usually due to downregulation or malfunctioning of IGF2, has pointed to HMGA2, PLAG1, and IGF2 as genes causally involved, and functional experiments show that HMGA2 promotes IGF2 expression in PLAG1-dependent as well as PLAG1-independent ways; this underlies the significance of this pathway (see also Section 3.2) in the regulation of growth during the fetal and postnatal periods [102] ( Figure 3A).…”
Section: Hmga Dysregulation and Its Impact On Body Sizementioning
confidence: 99%
“…In 65% of patients with SRS, an underlying molecular aberration can be detected, affecting imprinted and non-imprinted fetal growth factors and their cellular networks; 5%–10% of individuals have maternal uniparental disomy of chromosome 7 (matUPD7),8 and around 50% have loss of methylation (LOM) of the telomeric imprinting control region (H19/IGF2:IG‐DMR or imprinting centre 1 (IC1)) on 11p15.5 9. Rare cases have chromosome rearrangements involving IC110 or mutations in genes in the IGF2 pathway ( HMGA2, PLAG1 and IGF2 ) or CDKN1C 11–13. The heterogeneity in molecular aetiology partially explains differences in clinical presentation: for example, body asymmetry (tissue hypotrophy) and congenital anomalies (eg, hypospadias, uterine malformations) are more commonly associated with IC1 LOM,7 whereas heritable genetic changes underlie some familial cases,11 14 and verbal dyspraxia and dystonia/tremor are recognised in some cases with matUPD7.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, 23 deletions, detected by a-CGH, have been described. The remaining 5 cases were: a 7 bp deletion [11], a nonsense variant and a frameshift variant [10] and 2 deletions of exon 2 [12] and exons 1-2 [8]. The 23 deletions described so far range between 387 kb and 10.12 Mb, and involve other contiguous genes [9,[12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of HMGA proteins is high in early developmental stages in embryos and mesenchymal stem cells, whilst it is almost absent or very low in adult tissues. Additionally, several studies have showed their role in adipocytes differentiation and their overespression in some tumoral tissues [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%